A fundamentação do Logos hegeliano como experiência do pensar – - Cressoni, André (Revista Eletrônica Estudos Hegelianos, 2016)
ABSTRACT: Hegel’s idealism is well-known for its focus on the concept of idea permeating the whole system as its fundamental axis. Therefore, the concept of idea is granted the status of absolute, because it is unbound throughout all the levels and stages of development: logical, historical, political, religious and aesthetical. From this perspective, this paper intends to explore the meaning of the most fundamental level in which the concept of idea can be grasped: thought itself held fast in its pure conceptual level as logic. This results in a logos-thesis build in such a way as to respond to Modernity’s main lemmas and to surpass this same Modernity by radicalizing its own lemmas. In this context, we will analyze how Hegel’s dialectical idealism is linked to the idea of a critic of metaphysics, a critic of reason and to the critic of empiricism. These are the turning points of Kant’s transcendental idealism, seen by Hegel as the major expression of Modern Philosophy. Analyzing how Hegel approaches and distances himself from Kant’s viewpoint based on these pillars, we intend to show the foundation of Hegel’s thesis of an experience of pure thought or a logos-thesis.